Heterogeneous Belief Asset Pricing from the Perspective of Behavioural Finance: A Partial Differential Game Model with Interaction Terms (Contemporary Mathematics, 2025)
Asset pricing models have played an important role in the development of modern financial theory. From the Capital Asset Pricing Model (CAPM) to the Arbitrage Pricing Theory (APT), these classical models provide the basic framework for understanding and predicting asset prices. However, most traditional asset pricing models are based on the efficient market hypothesis, which assumes that all investors are rational, have homogeneous expectations, and can process all available information quickly and accurately. Despite their success in some respects, these models have proved inadequate in explaining and predicting market anomalies. For example, market bubbles, excessive volatility, and frequent deviations of asset prices from their fundamental values cannot be adequately explained by traditional rational expectations models. In order to more accurately capture the complex market dynamics, especially given the heterogeneous beliefs and their interactions between investors, this study uses of Partial Differential Equations (PDEs), deeply analyses the mechanism of heterogeneous beliefs influence. This study not only improves our understanding of how financial markets operate, but also provides a solid foundation for the development of effective risk management strategies and policy design. This study contributes to building a more robust and inclusive financial environment to better cope with future challenges and uncertainties.
Keywords: behavioural finance; heterogeneous effects; asset pricing